The long-term failure processes of a large reactivated landslide in the Xiluodu reservoir area based on InSAR technology - Li, Lingjing; Yao, Xin; Wen, Baoping; Zhou, Zhenkai; Li, Renjiang (Frontiers in Earth Science, 2023)
After the first impoundment of the reservoir, many landslides seriously threatened the safety of the reservoir. Accurate determination of the relationship between the landslide deformation characteristics and water-level fluctuations is crucial. However, with the increasing number of water-level fluctuation cycles, the deformation characteristics of the landslides were also changing, and long-term continuous monitoring to capture the progressive failure process of reservoir landslides is necessary. A large reacted landslide in the Xiluodu reservoir was set as an example, using InSAR technology to seek its variations of deformation characteristics over nine years. The local deformation rate and annual maximum deformation area variation were analyzed by InSAR technology based on Sentinel-1 descending SAR data from October 2014 to June 2022. According to the regional deformation characteristics, the landslide was divided into three zones: Zone I above the elevation of 950 m; Zone II below it; the front edge of Zone II, where the collapse happened, was further divided into Zone III. In general, the accumulated deformation in Zone I was the largest, followed by Zone III, and Zone II was the smallest. The average deformation rate of Zone II was the smallest. Zone I of NLJL was mainly affected by the drawdown of reservoir water level, and the impacts of water-level rising and drawdown on Zone II and Zone III were similar. After analyzing a nine-year variation of the deformation area, the deformation mechanism of NLJL changed from a retrogressive type to a progressive one after the first impoundment and then changed back to a retrogressive one after 2017. The impact of reservoir impoundment on NLJL was most substantial in the first three years after the first impoundment.